Seemanchali sheep : An untapped germplasm in Eastern region of Bihar - CHANDRAN, P C; KAMAL, REENA; DEY, A; KUMARI, RAJNI; KUMAR, PANKAJ (The Indian Journal of Animal Sciences, 2022)
Seemanchali sheep, an unique and distinct germplasm, is distributed in Supaul, Araria and Purnea districts of Seemanchal region of Bihar. The coat colour of sheep was dark brown with patches of white markings throughout the body. The body of the sheep, except the ventral surface, was covered with coarse wool, which is being sheared on regular interval. An average flock size was 36.5 with the range from 22 to 58. The estimated population size of Seemanchali sheep in the breeding tract was 20,000. The height at withers, body length and chest girth of Seemanchali sheep at 3 months of age were 50.34Â±0.25 cm, 48.22Â±0.31 cm and 55.46Â±0.28 cm; and 50.15Â±0.25 cm, 47.53Â±0.30 cm and 54.87Â±0.28 cm, respectively for male and female lambs. The same biometrical measurements at 12 months of age increased to 67.16Â±0.45 cm, 63.64Â±0.46 cm and 71.96Â±0.46 cm; and 63.16Â±0.22 cm, 60.44Â±0.23 cm and 64.19Â±0.23 cm, respectively for male and female lambs. Body weights of the lambs at 3 and 12 months of ages were 9.58Â±0.28 kg and 28.13Â±0.38 kg for ram lambs and 8.95Â±0.15 kg and 24.86Â±0.23 kg for ewe lambs, respectively. The age at 1st mating, age at 1st lambing and lambing intervals of Seemanchali sheep were found to be 14.6 months, 19.3 months and 11.2 months, respectively. Lambing percentage studied across the breeding tract was observed as 72.5. Large farmers possessing more than 100 Seemanchali sheep generated more than 90 per cent of their household income through Seemanchali sheep. Strategies to enhance the productivity of Seemanchali sheep vis-Ã -vis livelihood status of sheep farmers have been discussed.